Combined cardiac anomalies in Noonan syndrome: A case report. (2020) - H.S., Natraj Setty; S., Shankar; Patil, Rahul; Jadhav, Santosh; M.C., Yeriswamy; Reddy, Babu; Kharge, Jayashree; Raghu, T.R.; Shankar, Sandeep; Raj, Sathwik; N., Chethan; M., Nithin; et al.
Highlights: Noonan syndrome is the second most common syndromic cause of CHD. We present a rare case of Noonan syndrome having a combination of ASD, PS and HCM. Patient underwent balloon valvotomy for pulmonary stenosis. The patient is under regular follow-up and awaiting heart transplant. Abstract: Introduction: Noonan syndrome is the second most common syndromic cause of congenital heart disease. Most patients have an autosomal dominant inheritance, but some cases may be sporadic. Pulmonary stenosis is the most common cardiac manifestation in Noonan syndrome, associated with the atrial septal defect and hypertrophic cardiomyopathy. A combination of these three is present only in 5% of patients. Presentation of case: We report a case of a 21-year-old female who presented to our hospital concomitant cardiac lesions associated with pulmonary stenosis, atrial septal defect, and hypertrophic cardiomyopathy. This combination of cardiac defects is an infrequent manifestation of Noonan syndrome. The patient presented with complaints of exertion syncope over the past two years. 2D-Echocardiography showed biventricular hypertrophy, dysplastic pulmonary valve, severe pulmonary stenosis, asymmetric septal hypertrophy and large atrial septal defect. The genetic analysis report showed autosomal dominant inheritance with Ras/MAPK (mitogen-activated protein kinase) Positive. Discussion: Due to the wide spectrum of symptoms and presentations in Noonan cases, accurate clinical and genetic diagnosis, and comprehensive management of the disorder are strongly recommended. Conclusion: We have described a case of rare combination of cardiovascular defects in Noonan Syndrome with a view to achieve better insight into the disease course and advantages of timely treatment and follow up. Our patient is currently in follow-up after treatment with percutaneous balloon pulmonary valvuloplasty, has improved symptoms, and is awaiting heart transplant.